Laboratory confirmation of Buruli ulcer cases in Ghana, 2008-2016. - Dorothy Yeboah-Manu; Sammy Yaw Aboagye; Prince Asare; Adwoa Asante-Poku; Kobina Ampah; Emelia Danso; Evelyn Owusu-Mireku; Zuleihatu Nakobu; Edwin Ampadu (Public Library of Science (PLoS), 2018)
Buruli ulcer (BU), a necrotizing skin infection caused by Mycobacterium ulcerans is the third most important mycobacterial disease globally after tuberculosis and leprosy in immune competent individuals. This study reports on the retrospective analyses of microbiologically confirmed Buruli ulcer (BU) cases in seventy-five health facilities in Ghana.Pathological samples were collected from BU lesions and transported either through courier services or by car directly to the laboratory. Samples were processed and analysed by IS2404 PCR, culture and Ziehl-Neelsen staining for detection of acid-fast bacilli. From 2008 to 2016, we analysed by PCR, 2,287 samples of 2,203 cases from seventy-five health facilities in seven regions of Ghana (Ashanti, Brong Ahafo, Central, Eastern, Greater Accra, Northern and Volta). The mean annual positivity rate was 46.2% and ranged between 14.6% and 76.2%. The yearly positivity rates from 2008 to 2016 were 52.3%, 76.2%, 56.7%, 53.8%, 41.2%, 41.5%, 22.9%, 28.5% and 14.6% respectively. Of the 1,020 confirmed cases, the ratio of female to male was 518 and 502 respectively. Patients who were 15 years of age and below accounted for 39.8% of all cases. The median age was 20 years (IQR = 10-43). Ulcerative lesions were 69.2%, nodule (9.6%), plaque (2.9%), oedema (2.5%), osteomyelitis (1.1%), ulcer/oedema (9.5%) and ulcer/plaque (5.2%). Lesions frequently occurred on the lower limbs (57%) followed by the upper limbs (38%), the neck and head (3%) and the least found on the abdomen (2%).Our findings show a decline in microbiological confirmed rates over the years and therefore call for intensive education on case recognition to prevent over-diagnosis as BU cases decline.